Enhancing Loud Reading Skills In English Language Among Second Language Learners (A Study Based On Grade Six Students At KM/KM/ Shams Central College (National School), Maruthamunai) - M.I Ayas Ahamed; M.J Fathima Sujani; M.H.M Majid; M.R Rishad Muhammed (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Reading Aloud strategy used in the teaching reading skills, which means the teachers and students pronounced the word loudly in front of the class to get the information. The study aimed to enhance the loud reading skills in English among second language learners, specifically grade 6 students at KM/KM/Shams Central College, Maruthamunai. The objectives of the research were; to identify pronunciation difficulties encountered by the students of KM/KM/Shams Central College, Maruthamunai, to identify the factors influence on their loud reading skills, to assist students in improving loud reading skills and to assess the best strategies for enhancing their loud reading easily. The research involved a sample of 20 students after the pre-test and data was collected through a loud reading test and interviews. The data collected was analyzed in MS Excel. According to this research the findings were; pronunciation difficulties and factors influencing loud reading skills; students' struggles with pronunciation impacted their confidence and participation in English classes and it highlighted the impact of teachers' teaching methods on students' reading abilities and their attitudes towards reading. Positive attitudes towards reading were found to significantly aid in students' literacy development, while negative experiences could hinder progress. The comparison of pre-test and post-test marks further supported the success of these strategies. The read aloud strategy was identified as an effective method for improving fluency and conveying meaning through reading. The teachers' methodologies and attitudes towards reading significantly influence students' reading abilities. The study recommends introducing the research findings to grade 6 students and providing them with special attention and motivation to overcome reading difficulties. It suggests that through effective intervention, students can become fluent in learning English as a second language.